TINGKAT BAHAYA BANJIR DI KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Yoga Rahmata; Triyatno Triyatno (JURNAL BUANA, 2022)
This study aims to determine and map the flood hazard index in Bungus Teluk Kabung District, Padang City. This type of research is quantitative descriptive using secondary data as a data source. The sample in this study is a land unit located in the Bungus Bay Kabung sub-district which was taken by total sampling. The data is analyzed by overlaying the map to determine the level of flood hazard. The results of this study found that the flood hazard zoning in Bungus Teluk Kabung Subdistrict, West Sumatra Province is divided into 2 zones, namely, a medium-prone zone with an area of ​​61.8 Km2 and a high-prone zone with an area of ​​15.87.Km2. The moderate flood hazard zone in the Bungus Teluk Kabung sub-district is spread over 6 sub-districts. Most of the moderate danger zones are located in Teluk Kabung Tengah Village with an area of ​​13.5 km2, Teluk Kabung Selatan 12.03 km2, Teluk Kabung Utara 9.06 km2. Meanwhile, the high flood hazard zone in the Bungus Teluk Kabung sub-district is spread over 6 sub-districts. Most of the high hazard zones are located in the Bungus Barat sub-district with an area of ​​12.43 km2, East Bungus 6.64 km2, and Teluk Kabung Utara 1.8 km2.